Management Geography Asian Perspectives Focusing on Japan and Surrounding Regions - Taira, Atsushi; Schlunze, Rolf D. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Management geography explores the spatial characteristics of management-related issues, especially of firms. This book discusses management geography in Japan and other Asian countries from Asian perspectives. The field has made significant contributions to the global economy but has not been deeply investigated in English-language geographical literature to date. The book addresses the following critical questions: What kinds of challenges do multinational corporations in Japan and other Asian countries face? How are managerial actors in multinational enterprises (MNEs) embracing boundary-spanning activities in a global context? How do firms and related entities cultivate business pipelines and 'buzz' within and beyond local regions? How do actors in Japanese MNEs, small- and medium-sized enterprises (SMEs) and related institutions embed various managerial processes at overseas locations? This book consists of two parts: Part I discusses the application and roles of Japanese and international managerial practices in the globalizing world. Part II examines changing business communities in the industrial and rural spaces of East Asia, focusing primarily on Japan and China. This work will interest readers in a wide range of fields, including geography, management studies, economics, urban planning and sociology. The book is also suitable for upper-level undergraduate students and graduate students in geography, management studies and related fields.
Introduction: Management geography-An Asian perspective focusing on Japan and surrounding regions -- Performance analysis of boundary spanners in multinational enterprises through the lens of management geography -- Changes in the locational conditions of the Japanese machinery and instrument industry in China: A case study of the Dalian Economic and Technological Development Zone -- Management issues in global R&D of Japanese chemical companies -- Small- and medium-sized "global-niche" firms in Japan: A key for the rejuvenation of Japan's local economy? -- Industrial agglomeration and regional development planning analysis by GIS in the city of Utsunomiya, Tochigi, Japan -- Unique functions of a metropolitan co-working space: A case study in Tokyo, Japan -- How customer service centers in foreign cities serving Japan changed their business?: A case study of the city of Dalian, China -- Factors influencing enterprise development in the inland regions of Fujian province in China -- Transformation of agricultural management in Japan under globalization pressure: A focus on product differentiation strategy. .
Keywords: Human geography; Management; Economics; Human Geography; Management; Economics